How to develop and manage your own community seed bank: Farmers’ handbook (updated version). Management, networking, policies and a final checklist: Booklet 3 of 3 - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon R.; Porcuna Ferrer, Anna (Bioversity International, 2020)
This handbook is a companion to Vernooy, R., Sthapit, B. and Bessette, G. (2020). Community seed banks: concept and practice. Facilitator handbook (updated version). Bioversity International, Rome, Italy (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Booklet 1 is available at: http://hdl.handle.net/10568/92000 ; Booklet 2 is available at: http://hdl.handle.net/10568/92001 .